Incidence of Central Line-Associated Bloodstream Infections (CLA-BSIs) in the Intensive Care Unit (ICU) at Benghazi Medical Centre - Mukhtad, Amal; Elramly, Asma; Al Kadiky, Amina; Al Mahguob , Noura; Eshaim , Heba; Al Musraty , Asia (Libyan Journal of Public Health Practices, 2024)
Critically ill hospitalized patients have a significant risk of developing nosocomial bloodstream infections; most of these BSIs are usually from an intravascular device, Central-line-associated bloodstream infection is one of the most important problems in intensive care units worldwide. The study aimed to measure the incidence, risk factors, and most frequent causative organisms of central line-associated bloodstream infections in the Medical Intensive Care Units at Benghazi Medical Centre. This prospective study included 124 patients and was conducted between September 2021 and February 2022 in the Medical Intensive Care Units at Benghazi Medical Centre. The data was collected by using two research tools, worksheet for recording the data on each ICU patient with a central line and blood samples collected from patients using strict aseptic technique and sterile equipment. The total incidence rate of CLA-BSI in internal Intensive Care Units at Benghazi Medical Centre was 12.4/1000 CL-days, and the infection rate of CLA-BSI in patients' blood cultures after CVC insertion was 11.3%. Gram-negative bacteria were the most causative microorganisms by 54.4%, and 45.6% of the infection was gram-positive bacteria. Klebsiella pneumoniae was the most causative microorganism in gram-negative bacteria by 35%. While 28.1% of gram-positive bacteria were Staphylococcus aureus. Klebsiella pneumoniae and Staphylococcus epidermidis reported resistance to most of the tested antibiotics. CLA-BSI is an important cause of mortality in ICU patients. Patients with CLABSIs can have a longer hospital stay and higher health care costs. Thus, implementing standard infection prevention practices for critically ill patients is highly recommended